Identification of phenolic compounds and evaluation of biological activities of methanolic extracts obtained from two varieties of longan (Dimocarpus longan) peels - Chantarasaka, S.; Chareonsap, P. P.; Poeaim, S. (International Journal of Agricultural Technology, 2022)
Dimocarpus longan belongs to the Sapindaceae family, which are revealed as cryptic species. In Thailand, Dimocarpus longan spp. longan var. longan such as Edor is the most cultivated. Another Dimocarpus longan spp. longan var. obtusus (Dimocarpus obtusus), called Lum-Yai Thao, is found in Eastern Thailand. However, there is still little information on the biological activity of Thao. Hence, this research was designed to identify phenolic compounds and evaluate the biological activities of methanolic extracts obtained from peels of two longan varieties: Edor VS Thao. For the total phenolic compound, no significant differences were observed between Edor and Thao. For antioxidant activity using DPPH, ABTS, and FRAP assays, the analogs showed Edor had more activity than Thao. The disc diffusion test at 5 mg/disc showed that Edor peels extract effectively inhibited the growth of bacteria, but not Thao extracts which were strong against Propionibacterium acnes. However, both of them also did not have activity against Escherichia coli and Staphylococcus epidermidis.For anti-tyrosinase activity, both variety extracts had less effective anti-tyrosinase activity. In addition, anti-inflammatory activity was evaluated by measuring nitric oxide (NO) generated from SNP and using LPS-stimulated RAW 264.7 cells which showed excellent activity.In cytotoxicity using MTT assay, the results demonstrated that the methanolic extract of longan peel from Thao exhibited low cytotoxicity against both L929 and HaCaT. On the other hand, the extract from Edor exhibited cytotoxic activity. These results suggested that Thao peel extracts are different from Edor peel extract. Thao peel extracts showed excellent anti-inflammatory and little cytotoxic activity for L929 and HaCaT cell lines and antibacterial against P. acnes. Therefore, Thao peel extracts could be used in preparing products for anti-inflammatory supplements and cosmetics.